Molecular Identification of Endophytic Fungi Isolated from Bidara Root (Ziziphus mauritiana Lam.) Using Polymerase Chain Reaction (Pcr) - Jamaluddin, Siti Nurlillah; Fitriana, Fitriana; Amirah, Sitti (Journal Microbiology Science, 2024)
The roots of the bidara plant have the potential as antibacterial agents. The antibacterial compounds in the roots of the bidara plant originate from secondary metabolites produced by endophytic compounds known as endophytic fungi. The purpose of this research is to identify the types of endophytic fungi in bidara roots. The identification of microorganisms can be done through morphology or molecular methods. However, morphological identification alone is unable to depict the morphospecies to the phylogenetic level of a microorganism, thus molecular identification using the Polymerase Chain Reaction (PCR) method is required. This study utilized root isolates from the bidara plant with the sample code IFAZ-6, which, after sequencing, yielded a pair of base pairs measuring 558bp. The results of BLAST and phylogenetic analysis revealed that the IFAZ-6 isolate has a close relationship with the species Clonostachys rosea., which has been recorded in the database with a 100% identity level.